2017
DOI: 10.1016/j.redox.2017.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Exercise, oxidants, and antioxidants change the shape of the bell-shaped hormesis curve

Abstract: It is debated whether exercise-induced ROS production is obligatory to cause adaptive response. It is also claimed that antioxidant treatment could eliminate the adaptive response, which appears to be systemic and reportedly reduces the incidence of a wide range of diseases. Here we suggest that if the antioxidant treatment occurs before the physiological function-ROS dose-response curve reaches peak level, the antioxidants can attenuate function. On the other hand, if the antioxidant treatment takes place aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
111
0
5

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(120 citation statements)
references
References 67 publications
4
111
0
5
Order By: Relevance
“…It has been suggested that physiological changes, including the increment of oxidative stress caused by DM and other chronic diseases, originate a phenomenon known as hormesis 22 . Hormesis is the process by which biological systems react to the exposition of chemicals, toxins, radiation and reactive oxygen species when these are modulated by aging and is reflected by a greater adaptation capacity and a better tolerance to stressing factors 23 . This could be the case for DM and the increase in blood glucose that in turn favours an increase in oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that physiological changes, including the increment of oxidative stress caused by DM and other chronic diseases, originate a phenomenon known as hormesis 22 . Hormesis is the process by which biological systems react to the exposition of chemicals, toxins, radiation and reactive oxygen species when these are modulated by aging and is reflected by a greater adaptation capacity and a better tolerance to stressing factors 23 . This could be the case for DM and the increase in blood glucose that in turn favours an increase in oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Showing anticancer, antimicrobial, and antiviral activities, certain RCS are suggested to be promising as potential therapeutic agents [8,9]. Increasing evidence indicates that different reactive species (e.g., oxygen-, nitrogen-, and sulfur-containing molecules) trigger hormetic response [10,11]; however, possible involvement of RCS has not been intensively investigated. It is clear from many studies that RCS can modulate cell signaling pathways, including the stress responses, proapoptotic processes, enzyme activities, and transcription factor functions in different experimental models [9,[12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…For hormesis to exist, there is conceptually an assumed threshold and the question becomes whether such a threshold exists in the assumed model that matches reality (Cox, 1987; Slob, 1999). Such an issue was discussed as early as 1971 in Hatch (1971) and continues to today in disciplines such as aging, biology, crop growth, environmental science, food chemistry, material science, medicine, pharmaceutical sciences, radiation physics, technology; some recent examples include Vaiserman (2011); Radak et al (2017); Zou et al (2017); Sthijns et al (2017); Abbas et al (2017); Roullier-Gall et al (2016); Ji et al (2016).…”
Section: Introductionmentioning
confidence: 99%
“…As the dose increases, the shapes of the mean toxicological response can vary from J-shaped to inverted U-shaped with different threshold models (Goetghebeur and Pocock, 1995; Hunt and Rai, 2005; Ulm, 1991). There is also recent research that suggests exercise, oxidants and antioxidants may change the shape of a belled shape hormetic response curve (Radak et al , 2017). …”
Section: Introductionmentioning
confidence: 99%